Mangrove wetlands distribution status identification, changing trend analyzation and carbon storage assessment of China - Chang Li; Fu Wang; Peng Yang; Fei-cui Wang; Yun-zhuang Hu; Yan-lin Zhao; Li-zhu Tian; Rui-bin Zhao (China Geology)
This research investigates the ecological importance, changes, and status of mangrove wetlands along China’s coastline. Visual interpretation, geological surveys, and ISO clustering unsupervised classification methods are employed to interpret mangrove distribution from remote sensing images from 2021, utilizing ArcGIS software platform. Furthermore, the carbon storage capacity of mangrove wetlands is quantified using the carbon storage module of InVEST model. Results show that the mangrove wetlands in China covered an area of 278.85 km2 in 2021, predominantly distributed in Hainan, Guangxi, Guangdong, Fujian, Zhejiang, Taiwan, Hong Kong, and Macao. The total carbon storage is assessed at 2.11×106 t, with specific regional data provided. Trends since the 1950s reveal periods of increase, decrease, sharp decrease, and slight-steady increases in mangrove areas in China. An important finding is the predominant replacement of natural coastlines adjacent to mangrove wetlands by artificial ones, highlighting the need for creating suitable spaces for mangrove restoration. This study is poised to guide future mangrove-related investigations and conservation strategies.©2024 China Geology Editorial Office.